2021
DOI: 10.3390/pathogens10060710
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of SARS-CoV-2 Seroprevalence between Fall 2020 and February 2021 in Allegheny County, Western Pennsylvania, USA

Abstract: Seroprevalence studies are important for understanding the dynamics of local virus transmission and evaluating community immunity. To assess the seroprevalence for SARS-CoV-2 in Allegheny County, an urban/suburban county in Western PA, 393 human blood samples collected in Fall 2020 and February 2021 were examined for spike protein receptor-binding domain (RBD) and nucleocapsid protein (N) antibodies. All RBD-positive samples were evaluated for virus-specific neutralization activity. Our results showed a seropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[ 18 ] SARS-CoV-2 RBD IgG and IgA ELISA were performed as described with modifications defined in Supplemental Material. [ 19 ] This assay was optimized to detect anti-SARS-CoV-2 RBD IgG (cut-off titer ≥ 900) with sensitivity of 94.8% and specificity of 97.8% and IgA (cut-off titer ≥ 300) with sensitivity of 88.2% and specificity of 97.3% in blood. The limit of detection on this assay was 100; samples below the limit were set to 99 for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 ] SARS-CoV-2 RBD IgG and IgA ELISA were performed as described with modifications defined in Supplemental Material. [ 19 ] This assay was optimized to detect anti-SARS-CoV-2 RBD IgG (cut-off titer ≥ 900) with sensitivity of 94.8% and specificity of 97.8% and IgA (cut-off titer ≥ 300) with sensitivity of 88.2% and specificity of 97.3% in blood. The limit of detection on this assay was 100; samples below the limit were set to 99 for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Neutralization tests were performed as previously described [40]. Sera from a nonhuman primate previously vaccinated against SARS-CoV-2 and known to neutralize virus in this assay was included as a positive control.…”
Section: Focus Reduction Neutralization Test (Frnt)mentioning
confidence: 99%
“…In this Special Issue, five different publications [ 38 , 39 , 40 , 41 , 42 ] have characterized the antibody response at population and molecular levels, contributing to a broader picture of SARS-CoV-2 epidemiology. Xiao et al [ 38 ] conducted a large-scale screening of serum samples in the Guangdong province, China, between March and June 2020.…”
mentioning
confidence: 99%
“…The overall prevalence of virus-specific antibodies was low soon after the emergence of COVID-19 in Guangdong, suggesting an urgent need for vaccination to increase population immunity to SARS-CoV-2. Another study by Xu et al [ 39 ] revealed a 4.5-fold increase in SARS-CoV-2 seroprevalence from Fall 2020 to February 2021 in the population of Western Pennsylvania, USA, which was shown to be driven both by infection and vaccination. Kazachinskaia et al [ 40 ] analyzed the blood samples of COVID-19 patients in Novosibirsk city, Russia, and observed cross-reactivity of antibodies to SARS-CoV (2002) proteins.…”
mentioning
confidence: 99%